Development of quantum machine learning for protein structure prediction - Bianco, Nimbe Qureshi; Miyashita, Sierra-Sosa; Pathak, Pathak (Journal of Computer Science and Research (JoCoSiR), 2023)
Quantum Machine Learning (QML) holds immense potential in revolutionizing the prediction of protein structures, a critical challenge in computational biology. This research explores the application of quantum states, including superposition and entanglement, to capture the intricate and uncertain nature of protein conformations. Quantum gates and Fourier transforms are investigated as tools to manipulate and enhance quantum states, showcasing their ability to discern features essential for accurate predictions. The integration of hybrid quantum-classical models addresses the current limitations of quantum hardware, combining classical and quantum computing strengths. Quantum error correction is identified as a pivotal aspect for ensuring the reliability of predictions in the quantum domain. A numerical example is presented to illustrate the probabilistic nature of quantum states and the potential for obtaining optimized outcomes through quantum machine learning. The findings highlight the need for continued interdisciplinary collaboration between quantum physicists, computer scientists, and computational biologists to advance the field. While the exploration of QML for Protein Structure Prediction is in its early stages, the research emphasizes the transformative potential of quantum computing in unraveling the complexities of molecular structures.